Deceased donor uterus retrieval: A novel technique and workflow. Issue 3 (23rd September 2017) - Testa, G.; Anthony, T.; McKenna, G. J.; Koon, E. C.; Wallis, K.; Klintmalm, G. B.; Reese, J. C.; Johannesson, L.
Abstract : Uterus transplantation has proven successful when performed with a living donor. Subsequently, interest in the novel field of reproductive transplantation is growing. The procedure is still considered experimental, with fewer than 25 cases performed worldwide, and the techniques of both uterus procurement and transplantation are still developing. We detail a new approach to deceased donor uterus procurement. In contrast to reported techniques and our own initial experience, in which the deceased donor uterus was procured post cross‐clamp and after other organs were procured, our approach now is to perform the uterus procurement prior to the procurement of other organs in a multiorgan donor and hence prior to cross‐clamp. We describe our practical experience in developing and implementing the logistical workflow for deceased donor uterus procurement in a deceased multiorgan donor setting. Abstract : The authors describe a novel technique and logistical workflow of deceased donor uterus retrieval, where the uterus is procured prior to cross‐clamp and prior to the procurement of other organs in a multiorgan donor and is then successfully transplanted.